The quality of roasted and ground brazilian coffee: Chemical analysis of the effect of fixed mineral residue e different types of packaging on moisture content (Research, Society and Development, 2021)
The agricultural production of national coffee faces controversy regarding the quality of roasted and ground coffee, being susceptible to quality loss because of oxygen and humidity exposure and high storage temperatures. In light of the importance of coffee to the Brazilian economy and consumption, a survey was made of the main brands of coffee sold in establishments in the city of São Luís, observing the presence or absence of the ABIC quality seal, the category (traditional, extra-strong, superior, gourmet), and the most common packaging types (pillow and vacuum-sealed bags). Then, two purity parameters established by ABIC – humidity and fixed mineral residue – were determined quantitatively in the eight representative samples. The analyses were performed following the procedures described by the Adolf Lutz Institute (2008). The survey revealed that the superior and gourmet categories of coffee are not easily found, while traditional and extra-strong coffee is very accessible, both in pillow and vacuum-sealed bags. The moisture level results showed two brands (A2 and A3) within the standards established by INMETRO for coffee in both pillow and vacuum-sealed bags. Of the samples of fixed mineral residue that were collected, brand A1 was observed to be in conformity with legislation, for coffee packaged in both pillow and vacuum-sealed bags, and brand A4 showed results for pillow bags within the given parameters. Statistical design was applied to verify the effect of packaging (pillow and vacuum-sealed bag) on moisture levels between different brands using analysis of variance (ANOVA). The results showed that despite displaying the ABIC seal attesting to the quality of the product, without fraud and free of impurities, 50% of the samples analyzed showed alterations in moisture level and 62.5% showed fixed mineral residue levels above the standards established by Brazilian legislature.